2018
DOI: 10.1007/s40732-018-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of a Relational Training Intervention on Fluid Intelligence Among a Sample of Socially Disadvantaged Children in Bangladesh

Abstract: A growing consensus is that performances on standardized intelligence tests can be positively influenced by interventions that focus on improving relational reasoning. One such intervention, known as SMART (Strengthening Mental Abilities with Relational Training), consists of presenting participants with increasingly complex exemplars of relational reasoning tasks involving premises associated along same-as, opposite-of, more-than, and less-than relations. Following multiple training and testing sessions invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…However, participants in our study completed a mean of 27% of the training stages reported in other SMART studies (e.g., Cassidy et al, 2016Cassidy et al, , 2011Colbert et al, 2018;Hayes & Stewart, 2016). The degree to which our participants' NVIQ increased is roughly congruent with those studies, assuming that increases in intelligence due to relational training are linearly related to the amount of training completed (see also Amd and Roche (2018)).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, participants in our study completed a mean of 27% of the training stages reported in other SMART studies (e.g., Cassidy et al, 2016Cassidy et al, , 2011Colbert et al, 2018;Hayes & Stewart, 2016). The degree to which our participants' NVIQ increased is roughly congruent with those studies, assuming that increases in intelligence due to relational training are linearly related to the amount of training completed (see also Amd and Roche (2018)).…”
Section: Discussionsupporting
confidence: 82%
“…Even allowing for the fact that participants could engage with the relational training program in their own time if they wished, the total number of hours of exposure to training is much less than in some studies. Amd and Roche (2018) also employed a similar measure of NVIQ (i.e., Matrices) and correspondingly noted a possible relationship between number of stages of training completed and NVIQ gain. Furthermore, targeting a sample with such a youthful age range (6-10 years) was ambitious for this kind of intensive cognitive training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The training effects of SMART also appear to manifest in non-Western samples. For example, Amd and Roche (2018) provided SMART training to a sample of 35 socially disadvantaged children in Bangladesh and observed rises in fluid intelligence (as measured using Raven's Matrices). Furthermore, those who completed more training stages showed the greatest improvements in fluid intelligence.…”
Section: Introductionmentioning
confidence: 99%